Gamification: Stimulating User Smart City Application - Razie Razak; Radityo Muhamad; Pawito Pawito (Universitas Ahmad Dahlan, 2021)
The urban problems have led to an increase in the population in urban areas considering the needs of many government employees to provide service to all citizens. However, in actual conditions, government employees are limited, therefore, need community empowerment involved to support government management of the city. The solution for community empowerment is using communication technology as a public space for the citizens to communicate with the government. Citizen participation used smart city application ass public space to inform the sentiment public to the government. Citizens have adapted from traditional public play to public technological space. Gamification on smart city application devices motivates citizens, which has a growing influence on reporting and complaint activity. Technology set up gamification to create active citizens by reporting complaints of city infrastructure. Results identified gamification encourage a lot of citizen participation in reporting sentiment and complaint inside smart city applications.